DOES FISCAL DECENTRALIZATION POLICY PROMOTE ECONOMIC GROWTH IN INDONESIA DURING REFORM ERA? (An analysis of Specific-Purpose Grant) - Junaidi, Aang (Jurnal Ilmiah Administrasi Publik, 2013)
Abstract: Does Fiscal Decentralization Policy Promote Economic Growth In Indonesia During Reform Era?. Research findings concerning the impact of fiscal decentralization on economic growth are still debatable. On the one hand, some results reveal that fiscal decentralization contributes to economic growth. On the other hand, the other results show that fiscal decentralization has negative effect on economic growth. Furthermore, this research attempts to investigate whether Specific-Purpose Grant, one type of equalization funds, promotes economic growth in Indonesia during decentralization era. To achieve this objective, this research uses 33 provincial level panel data (an aggregate data of provincial, municipal, and district governments) during period 2002â2011, with the method of panel data regression analysis. This research finds out that there has been a statistically insignificant positive impact of Specific-Purpose Grant on economic growth in Indonesia. Furthermore, control variables such as investment, human capital, and workforce have significantly positive contribution to economic growth. Keywords: Fiscal Decentralization, Economic Growth, Specific-Purpose Grant, Panel Data Regression Analysis. Abstrak: Does Fiscal Decentralization Policy Promote Economic Growth In Indonesia During Reform Era?. Hasil temuan penelitian tentang dampak desentralisasi fiskal terhadap pertumbuhan ekonomi masih dapat diperdebatkan. Di satu sisi, beberapa temuan menginformasikan bahwa desentralisasi fiskal berkontribusi positif terhadap pertumbuhan ekonomi. Sebaliknya, hasil empiris lainnya menunjukkan bahwa desentralisasi fiskal berdampak negatif terhadap pertumbuhan ekonomi. Selanjutnya, penelitian ini mencoba untuk menguji apakah Dana Alokasi Khusus, salah satu jenis dana perimbangan, mendorong pertumbuhan ekonomi di Indonesia selama era desentralisasi. Untuk mencapai tujuan tersebut, penelitian ini menggunakan data panel 33-provinsi (gabungan data provinsi, kota dan kabupaten) selama periode 2002-2011 dengan metode analisis regresi data panel. Penelitian ini menemukan bahwa secara statistik terdapat dampak positif yang tidak signifikan Dana Alokasi Khusus terhadap pertumbuhan ekonomi di Indonesia. Selanjutnya, variabel kontrol seperti investasi, modal sumber daya manusia, dan tenaga kerja memiliki kontribusi positif yang signifikan terhadap pertumbuhan ekonomi. Kata Kunci: Desentralisasi Fiskal, Pertumbuhan Ekonomi, Dana Alokasi Khusus, Analisis Regresi Data Panel.